CHEMICAL AND CARBON-ISOTOPE INSTABILITY IN NATURAL GASES OF THE KIPYASHCHIY BUGOR MUD VOLCANO (SOUTHWESTERN TURKMENISTAN) - Voytov G.I.; Belikov V.M.; Orlova T.G.; Nosik L.P.; Kucher M.I.; Krivomazova N.G.; Nikulina I.V. (My University, 1989)
Mud volcanoes occupy a special place among natural phenomena. First, in terms of the scale of discharges of carbonaceous gases from them, the acute stage of their eruption is comparable to surface lava eruptions from cone volcanoes. Second, mud volcanoes are always associated with regions of alpine folding, and with the highest degree of present-day geodynamic activity. Third, all mud volcanoes are associated with first-order lineaments and their intersections, or with complex tectonic nodes. Fourth, mid volcanoes are associated with regions that have thick sedimentary sequences, primarily Tertiary or Neogene-Quaternary, although breccia fragments in the mud flows indicate that the 'roots' of some of the largest mud volcanoes, e.g., those of the South Caspian Basin and Azerbaijan, apparently extend into Mesozoic deposits. Fifth, there is a paragenetic association of mud volcano eruptions with the largest earthquakes that occur in the respective regions. Investigation of these phenomena is important in search for geochemical earthquake precursors and in understanding of generation and accumulation of oil and gas in the rocks of geodynamically active sedimentary basins. It also is relevant to the problem of evaluation of the material balance of carbonaceous and other gases in the mud volcano process.
Keywords: Neogene; Quaternary; Mesozoic; Кайнозой::Неоген; Cenozoic::Quaternary; Mesozoic; Cenozoic::Neogene; Мезозой; Кайнозой::Четвертичная